2011
DOI: 10.1007/s00264-010-1191-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers in the diagnosis of chondral defects following anterior cruciate ligament insufficiency

Abstract: The results suggest that uCTX-I, uCTX-II and sCOMP could identify patients with focal cartilage lesions from an early stage of osteoarthritis of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…4 Streich NA 12 reported increase in CTX I level is related with increase in local production of inflammatory cytokines resulting in uncoupling of bone turnover and finally cartilage degradation. 12 Increased levels of urinary CTX I indicates increased bone resorption in cases with progressive OA but not in non-progressive OA has been reported earlier. 7,8,13,14 Garnero P et al 15 reported that high baseline urinary CTX I independently predicts an increased risk of OA.…”
Section: Discussionmentioning
confidence: 68%
“…4 Streich NA 12 reported increase in CTX I level is related with increase in local production of inflammatory cytokines resulting in uncoupling of bone turnover and finally cartilage degradation. 12 Increased levels of urinary CTX I indicates increased bone resorption in cases with progressive OA but not in non-progressive OA has been reported earlier. 7,8,13,14 Garnero P et al 15 reported that high baseline urinary CTX I independently predicts an increased risk of OA.…”
Section: Discussionmentioning
confidence: 68%
“…Some data show that ACLinjured knees are at risk for degenerative changes at longterm follow-up whether the ligament is reconstructed or not [34,35]. Biomechanical markers of turnover of bone and cartilage have been investigated in blood and urine to identify focal cartilage lesions from an early stage of osteoarthritis after injury of the human ACL [36]. Degeneration seems to be caused by intra-articular processes induced at the time of ACL injury, combined with long-term dynamic joint loading changes [37].…”
Section: Discussionmentioning
confidence: 98%
“…Higher concentrations of pro-inflammatory biomarkers within synovial fluid were also found in patients with acute ACL injury who had associated cortical fractures identified on MR imaging 169 . At longer follow-up periods in patients with ACL tear, more severe cartilage damage on MR imaging was associated with increased serum biomarkers of bone and cartilage turnover 20 years after injury 170 and with increased serum concentrations of the small nucleolar RNA U38 1 year after injury 171 . Higher collagen cleavageto-synthesis ratio was also noted in patients with abnormal joint space width on knee radiographs 4 years after ACL injury 172 .…”
Section: Association Between Imaging Findings and Wet Biomarkers Follmentioning
confidence: 94%